MICROSTRIP ANTENNA DESIGN SIMULATION FOR WIRELESS FIDELITY APPLICATION 802.11A STANDARD ON 5.8 GHZ - Buwarda, Sukriyah (Department of Electrical Engineering, University of Patria Artha, 2018)
A simulation of microstrip antenna design for Wireless Fidelity (Wi-Fi) application has been done on standard 802.11a 5.8 GHz frequency. Simulation design using High Frequency Structural Simulator (HFSS) v.13. Microstrip antenna is widely used because it is simpler and easier to integrate with other devices. In this research, the rectangular microstrip structure with the irradiation element (patch) is made up of three rectangular parts with a total dimension of 60x35 mm from the perfect electric conductor material. The ground plane is placed at the bottom of the antenna structure with a total dimension of 65x40 mm with the same material as PEC (perfect electric conductor) patch. The feeding technique used is the center probe conductor which is placed in the middle of the irradiation element (patch) with the diameter of 1.5 mm and the height of 1.6 mm from the copper material. Dielectric of FR-4 Epoxy material with relative permitivity 4.4 constants. The design success parameter is evaluated from Voltage Standing Wave Ratio (VSWR) and Reflection Coefficient (S11). Simulation results show that the antenna can work on the 5.66 GHz frequency band to 5.91 GHz with bandwidth of 250 MHz. at a frequency of 5.8 GHz obtained the value of VSWR 1.14 with the reflection coefficient value S11 -23.19 dB. The electric field distribution (E-field) and the magnetic field (H-field) are the same in all directions in the radiation plane. HPBW is obtained with angle width 520. It is concluded that the designed microstrip antenna can be used on 802.11a standard Fidelity (Wi-Fi) frequency at 5.8 GHz frequency.